Is Higher Better - Evaluating VAT Rate Hikes Through Buoyancy In Indonesia - Grace Sicilia Muchtar; I Gusti Ayu Agung Dewi Sucitawathi Pinatih (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study investigates the effectiveness of Value Added Tax (VAT) rate increases in Indonesia by analyzing VAT revenue buoyancy and examining the key factors that influence its performance. Employing a quantitative research approach, the study utilizes secondary time-series data from 2019 to 2024, sourced from the Directorate General of Taxes, Statistics Indonesia, and the Ministry of Finance of the Republic of Indonesia. A regression-based analysis is conducted to measure the responsiveness of VAT revenue to economic growth, taxpayer compliance, inflation, and tax administrative policies. Tax buoyancy serves as the primary indicator for evaluating the effectiveness of the 2022 VAT rate increase policy. The findings demonstrate that the VAT rate increase has proven effective in the short to medium term, with buoyancy values consistently exceeding one since policy implementation, indicating that VAT revenue growth has outpaced economic growth. Nevertheless, the sustainability of this effectiveness depends not only on rate adjustments but also on structural factors, including taxpayer compliance, administrative reforms, and the broadening of the VAT base. The planned selective increase of the VAT rate to 12 percent in 2025 reflects the government’s cautious approach to balancing revenue generation with fairness considerations, although its impact on VAT buoyancy is expected to be moderate. Empirical results further highlight the critical role of taxpayer compliance in ensuring the success of VAT policy. The introduction of the Coretax system by the Directorate General of Taxes is identified as a strategic step to strengthen administration and enhance compliance. Despite the regression analysis showing multicollinearity among some variables, the overall direction of the relationships remains consistent. The study concludes that VAT revenue performance is shaped by the interplay of tax rates, compliance levels, and structural reforms, and it recommends future research with expanded datasets and refined analytical techniques to provide deeper insights into the long-term effectiveness of VAT policies.